Growth and welfare effects of business cycles in economies with idiosyncratic human capital risk - Tom Krebs (Brown University, Department of Economics, 2002)
This paper uses a tractable macroeconomic model with idiosyncratic human capital risk and incomplete markets to analyze the growth and welfare effects of business cycles. The analysis is based on the assumption that the elimination of business cycles eliminates the variation in idiosyncratic risk. The paper shows that a reduction in the variation in idiosyncratic risk decreases the ratio of physical to human capital and increases the total investment return and welfare. If the degree of risk aversion is less than or equal to one, then economic growth is enhanced. This paper also provides a quantitative assessment of the macroeconomic effects of business cycles based on a calibrated version of the model. Even for relatively small degrees of risk aversion (around one) the model implies that the elimination of business cycles has substantial effects on investment in physical and human capital, economic growth, and welfare.
Keywords: D52; E32; O40; 330; Cost of Business Cycles; Growth; Idiosyncratic Risk; Konjunktur; Wirtschaftswachstum; Wohlfahrtsanalyse; Humankapital; Risiko; Theorie